A Single Center Retrospective Cohort Study Comparing Different Anticoagulants for the Treatment of Catheter-Related Thrombosis of the Upper Extremities in Women With Gynecologic and Breast Cancer - Porfidia, Angelo; Cammà, Giulia; Coletta, Nicola; Bigossi, Margherita; Giarretta, Igor; Lupascu, Andrea; Scaletta, Giuseppe; Porceddu, Enrica; Tondi, Paolo; Scambia, Giovanni; Ferrandina, Gabriella; Pola, Roberto (Frontiers in Cardiovascular Medicine, 2022)
Background: Catheter-related thrombosis (CRT) of the upper extremities is a frequent complication among cancer patients that carry a central venous catheter (CVC) and may lead to pulmonary embolism (PE) and loss of CVC function. Despite its clinical impact, no anticoagulant treatment scheme has been rigorously evaluated in these patients. In addition, there is no proven evidence that direct oral anticoagulants (DOACs) are efficacious and safe in this setting because cancer patients with CRT of the upper extremities were not included in the clinical trials that led to the approval of DOACs for the treatment of cancer-associated venous thromboembolism (VTE). Methods: We performed a single center retrospective cohort study on women with gynecologic or breast cancer treated with either low-molecular-weight heparin, fondaparinux, or DOACs for CRT of the upper extremities. Only patients who received anticoagulation at the proper therapeutic dose and for at least 3 months were included in the analysis. Effectiveness was evaluated in terms of preservation of line function, residual thrombosis, and recurrence of VTE (including PE). Safety was evaluated in terms of death, major bleeding (MB), and clinically relevant non‐major bleeding (CRNMB). Results: We identified 74 women who fulfilled the criteria to be included in the analysis. Of these, 31 (41.9%) had been treated with fondaparinux, 21 (28.4%) with enoxaparin, and 22 (29.7%) with the DOAC edoxaban. We found no differences between patients treated with the three different therapeutic approaches, in terms of preservation of line function, incidence of residual thrombosis, and VTE recurrence (including PE). Safety was similar as well, with no MBs recorded in any treatment group. Conclusion: These results, although retrospective and based on a relatively small sample size, indicate that, in women with gynecologic or breast cancer, CRT of the upper extremities may be treated with similar effectiveness and safety with fondaparinux, enoxaparin, and edoxaban. Further studies are needed to substantiate these findings.